2010
DOI: 10.1038/hr.2010.29
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between number of metabolic syndrome components and dietary factors in middle-aged and elderly Japanese subjects

Abstract: Metabolic syndrome (MetS) represents a cluster of risk factors for atherosclerosis and is considered a risk factor for cardiovascular disease. The role of diet in the etiology of MetS is poorly understood, especially among Asian subjects. This cross-sectional study assessed the relationship between diet and the number of MetS components among Japanese men (n¼609) and women (n¼631). Mean (s.d.) age and body mass index were 57.1 (12.1) years and 22.8 (2.8) kg m À2 for men and 55.5 (12.0) years and 22.0 (3.0) kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 55 publications
4
19
0
Order By: Relevance
“…The protective association with westernized breakfast pattern may represent beneficial effects of some foods or nutrients contributing to the dietary pattern. In a previous Japanese study, milk and dairy food consumption, an important contributor to the westernized breakfast pattern in the present study, was inversely associated with the numbers of metabolic syndrome components [37]. Moreover, in cross-sectional [38] and prospective [8,39] studies among non-Japanese populations, dairy product consumption has been protectively associated with metabolic syndrome.…”
Section: Discussionsupporting
confidence: 58%
“…The protective association with westernized breakfast pattern may represent beneficial effects of some foods or nutrients contributing to the dietary pattern. In a previous Japanese study, milk and dairy food consumption, an important contributor to the westernized breakfast pattern in the present study, was inversely associated with the numbers of metabolic syndrome components [37]. Moreover, in cross-sectional [38] and prospective [8,39] studies among non-Japanese populations, dairy product consumption has been protectively associated with metabolic syndrome.…”
Section: Discussionsupporting
confidence: 58%
“…van Meijl et al (16) reported that various cross-sectional studies support an inverse association between dairy product consumption and the prevalence of MetS in some, but not all, populations. Recently, Otsuka et al (18) examined the association between the number of MetS components and dietary factors in community-dwelling middle-aged and elderly Japanese subjects. In this cross-sectional study, a low intake of calcium, milk, and dairy products was associated with a high number of MetS components after adjusting for possible confounders, particularly in women.…”
Section: Discussionmentioning
confidence: 99%
“…Known risk factors for metabolic syndrome include age, obesity, diet, dietary patterns across life stages, and lack of exercise with variation in the prevalence observed across gender and ethnic groups (Park et al, 2003; Josse et al, 2008; Otsuka et al, 2010; Li et al, 2011; Beltran-Sanchez et al, 2013). Current smoking has been associated with the presence of insulin resistance, diabetes and metabolic syndrome (Facchini et al, 1992; Will et al, 2001; Park et al, 2003; Weitzman et al, 2005) whereas alcohol consumption appears to be protective to some extent (Liu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%